Pendekatan Molecular Docking dalam Metode Penemuan Obat Berbasis Struktur: Sebuah Tinjauan - Adha Dastu Illahi; Tifany Maulida Candra (Pharmaceutical and Biomedical Sciences Journal (PBSJ), 2026)
Molecular docking is one of the most widely used computational techniques in computer-aided drug design (CADD) for predicting ligand binding modes and relative binding affinities toward target proteins. Although binding affinity is frequently used to evaluate docking performance, the success of molecular docking cannot be determined by a single parameter. Instead, predictive accuracy depends on the integration of multiple interrelated methodological factors. This review discusses the fundamental principles, methodologies, validation strategies, and interpretation of molecular docking in the context of structure-based drug discovery. The topics covered include protein structure quality, conformational search algorithms, scoring functions, docking workflows, and protein–ligand interaction analysis. This review highlights that the accuracy of molecular docking relies on the integration of all methodological stages, from protein structure selection to validation and result interpretation. It provides a comprehensive overview of molecular docking as an effective tool for initial screening and hypothesis generation in structure-based drug discovery prior to further validation using molecular dynamics simulations and experimental studies.